ACCURACY OF CANCER ANTIGEN 125 AND ALBUMIN BEFORE OPERATION TO PREDICT THE OPERATION OUTCOME IN PATIENTS WITH ADVANCED STAGE EPITHELIAL TYPE OVARIAN CANCER - Budiana Budiana; Bayu Mahendra; Mega Putra; Harry Wijaya; Artana Putra; Nathassa Karisma (Jurnal Health Sains, 2023)
Ovarian cancer is a malignancy that grows and develops in the ovaries with a high mortality rate. Primary debulking surgery (P.D.S.) is diagnostic and therapeutic and has become the standard option. CA-125 levels were increasing with the worsening disease conditions in ovarian cancer. In addition, preoperative albumin levels were strongly associated with worse ovarian cancer outcomes. This study assessed the prediction of CA-125 markers and albumin levels on P.D.S. outcomes. This research is a diagnostic test conducted at Prof. Dr I.G.N.G. Ngoerah Hospital. The study sample consisted of 50 women aged 18 and over who underwent P.D.S. from 2018 to 2020 with P.A. results of advanced stage (III-IV) epithelial-type ovarian cancer. CA-125 and albumin levels were assessed before surgery and compared with the findings of P.D.S., which were grouped into suboptimal debulking and optimal debulking. There were no significant differences in the characteristics of the two groups. The accuracy of CA-125 levels on the outcome of P.D.S. surgery with a sensitivity of 75.6%, specificity of 55.6%, PPV of 88.6%, N.P.V. of 35.3% and accuracy of 72%. While the accuracy of albumin levels on the outcome of P.D.S. surgery with a sensitivity of 55.6%, specificity of 51.2%, PPV of 20%, N.P.V. of 84% and accuracy of 52%. CA-125 levels were higher in the suboptimal group but not statistically significant, but the sensitivity (70%) and specificity (80%) were still high, so they still have diagnostic value for ovarian cancer. The relationship between albumin levels and ovarian cancer is multifactorial, so it cannot be used to predict surgical outcomes